Determinant of Successful Tuberculosis Treatment in Puskesmas Singosari in 2020-2022 - Diah Ayu Kamila; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari; Rara Warih Gayatri (Keluwih: Jurnal Kesehatan dan Kedokteran, 2023)
Abstract—Indonesia is one of the countries that contribute the most mortality of TB in the world. The tuberculosis treatment success rate in Indonesia is 86% meanwhile is still far from the target coverage of the TB treatment success rate (90%). This study conducted to determine the determinant factors of successful TB treatment in Puskesmas Singosari. A cross-sectional design study was constructed for this study and used SITB and form TB as a research instrument. The population of this study were all drug-susceptible TB patients who had completed treatment at the Puskesmas Singosari in 2020, 2021, and QI-QII in 2022. The sample of this study was 71 people from 99 total population. The dependent variable is the success of drug-susceptible TB treatment. Independent variables are sex, age, weight, regular use of anti-tuberculosis drugs, and comorbidities. The data processing and analysis are being conducted using SPSS software. Chi-square analysis showed that the variable weight changes have a significant assosiation to successful tuberculosis treatment (p = 0,014; OR = 9,818). Puskesmas Singosari's TB Team can collaborate with the nutritionist team to optimize TB treatment by monitoring nutritional status and weight gain of drug-susceptible TB patients. Keywords: tuberculosis, drug-susceptible, successful treatment, determinant Abstrak—Indonesia termasuk salah satu negara penyumbang sebagian besar kasus kematian TB secara global. Persentase keberhasilan pengobatan TB di Indonesia ialah 86%, dimana masih jauh dari target cakupan keberhasilan pengobatan TB (90%). Penelitian ini dilaksanakan untuk mengetahui faktor determinan yang berhubungan dengan keberhasilan pengobatan TB Sensitif Obat di Puskesmas Singosari. Desain studi cross sectional digunakan dengan data sekunder bersumber dari SITB dan arsip formulir TB. Populasi dari penelitian ini adalah seluruh pasien TB-SO yang telah menyelesaikan pengobatan di Puskesmas Singosari pada tahun 2020, 2021, dan TW I-II tahun 2022. Sampel penelitian berjumlah 71 orang dari total populasi 99 orang. Variabel terikat dari penelitian ini yaitu keberhasilan pengobatan TB-SO. Variabel bebas yang diteliti yaitu jenis kelamin, usia, BB awal pengobatan, perubahan BB selama pengobatan, keteraturan minum OAT, dan komorbid. Hasil analisis membuktikan bahwa variabel perubahan berat badan berhubungan secara signifikan dengan keberhasilan pengobatan TB (p = 0,014; OR = 9,818). Rata-rata kenaikan berat badan pada pasien yang berhasil menjalani pengobatan TB adalah sebesar 2,19 kg. Tim P2TB Puskesmas Singosari dapat bekerjasama dengan program gizi masyarakat dalam optimalisasi pengobatan pasien TB melalui pemantauan status gizi dan kenaikan BB Pasien. Kata kunci: tuberkulosis, sensitif obat, keberhasilan pengobatan, determinan